The Diversity of Understorey Plants In Siranggas Wildlife Reserve, Pakpak Bharat District, North Sumatra - Nurul Annisa Br. Nasution; Etti Sartina Siregar (Talenta Publisher, 2024)
Information on the diversity of understorey plants in Siranggas Wildlife Sanctuary is still limited. This research was carried out to determine the diversity of understory at the Siranggas Wildlife Sanctuary Area, Pakpak Bharat Regency, North Sumatra. The study was conducted using purposive sampling method, with 5 sampling sites. Twenty plots measuring 2m x 2m were placed at each site to obtain a total 100 plots. The result showed that there were 41 species of understory plants found in the Siranggas Wildlife reserve, consisting of two division namely Pteridophytes (10 species) and Spermatophytes (31 species). The highest Important Value Index (IVI) value of understory plants in the study was obtained for Selaginella intermedia at 28,6%. The diversity index of all understory plants in the study was categorized as moderate level at value 2,88. The understory plants uniformity index was relatively high at 0,77. The species of understory plants in the study area must be preserved to maintain their sustainability.